Effects of dupilumab on quality of life in patients with atopic dermatitis: a systematic review and meta-analysis of randomized controlled trials - Sun, Yunqing; Liu, Haibo; Gao, Yingjun; Sang, Hong; Kong, Qingtao (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the impact of dupilumab treatment on the quality of life, psychological factors and clinical symptoms, in patients with moderate-to-severe atopic dermatitis.MethodsA comprehensive search was conducted in PubMed, Web of Science, Embase, and Cochrane Library. Data coverage extends until April 2024. The study exclusively encompassed randomized controlled trials. The primary outcome was the quality of life of patients, with subgroup analyses conducted. Revman 5.4 and Stata 15.1 software were used for the analyses.ResultsThis study included 17 studies with a total of 6,665 participants. To evaluate quality of life, six instruments were used: the Dermatology Life Quality Index (DLQI), the Quality of Life Index for Atopic Dermatitis (QoLIAD), the Children’s Dermatology Life Quality Index (CDLQI), the Infant’s Dermatitis Quality of Life Index (IDQoL), the Dermatitis Family Impact (DFI), and the EuroQol-5 Dimension (EQ-5D). The QoLIAD is specifically designed for atopic dermatitis. The results demonstrated that dupilumab significantly improved DLQI/QoLIAD scores in adult patients (SMD = −0.64, 95% CI [-0.84, −0.45], p < 0.00001), the CDLQI/IDQoL scores in children/adolescents (SMD = −0.73, 95% CI [-0.84, −0.63], p < 0.00001), family quality of life measured by DFI (SMD = −0.97, 95% CI [-1.20, −0.75], p < 0.00001), and EQ-5D scores (SMD = 0.64, 95% CI [0.46, 0.82], p < 0.00001). The study also reported significant improvements in sleep-related metrics, total score on the Hospital Anxiety and Depression Scale (HADS), HADS anxiety scale, and HADS depression score. Additional improvements were observed in the Patient-Oriented Eczema Measure (POEM), pruritus Numeric Rating Scale (NRS), Eczema Area and Severity Index (EASI), SCORing Atopic Dermatitis (SCORAD), percent Body Surface Area (BSA), Global Individual Sign Score (GISS), and Investigator’s Global Assessment (IGA) response.ConclusionOur study demonstrates that dupilumab significantly enhances patients’ quality of life and alleviates symptoms. This meta-analysis utilizes various assessment tools to evaluate quality of life, synthesizing data from recent clinical trials. It builds on prior research to provide a comprehensive analysis of dupilumab’s effects and overall efficacy. The aim of this study is to offer evidence-based insights to improve the clinical application of dupilumab.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/.